Physicochemical Properties of Balanites aegyptiaca (Laloub) Seed Oil - Fregon, Mohamed Elmustafa; Shakak, Mahdi Abbas Saad (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The main goal of this research was to study the physical and chemical properties of Balanites.aegyptiaca (laloub) oil.Two kilograms of Balanites aegyptiaca fruit were purchased from localmarket in Khartoum, Sudan. Fruits were then crushed using a steel hammer and seeds were thenobtained. One kilogram of seeds was collected and was then ground using grinding machine.Processed ground seeds were then eventually ready for further analysis.The results revealed thatB. aegyptiaca seed contain considerable percentage of moisture (3.10%) , oil (42.95%) ,protein(31.08%), fiber (12.64%), ash (3.19%) and carbohydrate (7.04%) on dry matter basis .Also theseeds contained different minerals e.g calcium (0.41mg), sodium (0.09mg), magnesium (0.13mg)phosphorus (0.30mg) and potassium (1.09mg) per 100g dry matter (DM).Also, the results of thephysicochemical evaluation of B. aegyptiaca oil showed that it contains viscosity 19.63 cp,density 0.9109 , refractive index 1.483, colour 7.633 (R.y.b), free fatty acid 3.06%, peroxidevalue 1.18 (meq O2 /kg) , saponification value 224.63 (mg KOH/g), iodine value 122.42 and acidvalue 1.53 (mg KOH/g). The fatty acid profile of B. aegyptiaca seed oil showed that it containslinoleic acid 34.36%, palmitic acid 13.37%, stearic acid 15.03% and oleic acid 28.57%.From the previous physicochemical tests of B,aegyptiaca oil could be used for edible purpose.